USING YOUTUBE VIDEOS TO TEACH WRITING - Nurhelfa, Sulistiawati; Herawati, Atti; Wahyuni, Asih (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2024)
This article aims to describe how an English teacher taught writing procedure text using YouTube videos to the 11th-grade students of Vocational High School. The study applied a descriptive qualitative approach. This research was conducted at one Vocational school in Pacet. The participants of this research were an English teacher and 36 students from grade 11 of Tourism Travel Business (ULP) major. This study was guided by one research question “How does the teacher teach writing procedure text using YouTube video to grade 11 students of Vocational High School?” The instruments used in this study were observation, documentation, and interview. The findings of this study show that: 1) the English teacher engaged the students to watch a video from YouTube together in the opening activity, 2) the English teacher and the students discussed the contents of the YouTube videos that have been watched in the core activity, and 3) the English teacher played YouTube videos to prepare the students’ mental condition before they were doing presentation about their writing project of procedure text in core activity. The results indicated that the YouTube video on teaching writing aligns with the stages of the teaching activities proposed by Rusmawan.